2023
DOI: 10.3233/jad-220460
|View full text |Cite
|
Sign up to set email alerts
|

Low Xanthophylls, Retinol, Lycopene, and Tocopherols in Grey and White Matter of Brains with Alzheimer’s Disease

Abstract: Background: Oxidative stress contributes to pathogenesis and progression of Alzheimer’s disease (AD). Higher levels of the dietary antioxidants— carotenoids and tocopherols— are associated with better cognitive functions and lower risk for AD, and lower levels of multiple carotenoids are found in serum and plasma of patients with AD. Although brains donated by individuals with mild cognitive impairment had significantly lower levels of lutein and beta-carotene, previous investigators found no significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 108 publications
0
0
1
1
Order By: Relevance
“…Contrary to some previous studies [ 58 , 59 ], we also found a positive association between plasma lycopene concentrations—a carotenoid biomarker—and AD risk, but only in individuals with a neurogenesis-centred biological susceptibility. However, overall, there is insufficient evidence to draw firm conclusions or tease apart direct effects of lycopene on future dementia risk [ 60 ], so it is presently unclear what this finding represents in the wider context of AD.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to some previous studies [ 58 , 59 ], we also found a positive association between plasma lycopene concentrations—a carotenoid biomarker—and AD risk, but only in individuals with a neurogenesis-centred biological susceptibility. However, overall, there is insufficient evidence to draw firm conclusions or tease apart direct effects of lycopene on future dementia risk [ 60 ], so it is presently unclear what this finding represents in the wider context of AD.…”
Section: Discussioncontrasting
confidence: 99%
“…Кроме того, было также показано, что как в сером (нейрональном), так и в белом (глиальном) веществе головного мозга (ГМ) пациентов с болезнью Альцгеймера (БА) или с до-клиническими лёгкими когнитивными нарушениями (КН) -значительно снижено содержание ликопина, ретинола, ксантофиллов (в частности, лютеина и зеаксантина), токоферолов [12].…”
Section: доказательная база по применению некоторых растительных пигм...unclassified